Molecular logic gates: the past, present and future - Erbas-Cakmak, Sundus; Kolemen, Safacan; Sedgwick, Adam C; Gunnlaugsson, Thorfinnur; James, Tony D; Yoon, Juyoung; Akkaya, Engin U (Chemical Society reviews, 2018)
The field of molecular logic gates originated 25 years ago, when A. P. de Silva published a seminal article in Nature. Stimulated by this ground breaking research, scientists were inspired to join the race to simulate the workings of the fundamental components of integrated circuits using molecules. The rules of this game of mimicry were flexible, and have evolved and morphed over the years. This tutorial review takes a look back on and provides an overview of the birth and growth of the field of molecular logics. Spinning-off from chemosensor research, molecular logic gates quickly proved themselves to be more than intellectual exercises and are now poised for many potential practical applications. The ultimate goal of this vein of research became clearer only recently - to "boldly go where no silicon-based logic gate has gone before" and seek out a new deeper understanding of life inside tissues and cells.